Risk Factors of HIV Infection in Pregnant Women at the Maternity of the Yaoundé Central Hospital - Fouedjio, Jeanne Hortence; Ymele Fouelifack, Florent; Dongmo Fouelifa, Loic; Mbu, Robinson (HEALTH SCIENCES AND DISEASE, 2017)
ABSTRACT Introduction and objectives. HIV infection affects millions of people worldwide, especially in sub-Saharan Africa. Transmission occurs by several means including the transmission from mother to child. The main objective of this study was to determine the risk factors of HIV infection among pregnant at the maternity unit of Yaoundé Central Hospital. Methods. We conducted an analytical cross-sectional study at the Obstetrics and Gynecologic Unit of the Yaoundé Central Hospital from 6th October 2015 to 30th June 2016. The sampling was consecutive. Testing was done by a sensitive test and a specific test if the first was positive. Data analysis was done through Excel 2007 software EpiData Analysis Version 3.2 and STATA version 12.0 (Texas USA 2001). Statistical significance was accepted for a value of P <0.05. Results. We included 360 pregnant women. Their average age was 27.99 +/- 5.63 years, ranging from 15 and 47 years. HIV prevalence was 13.1% (47/360). The main risk factors of HIV infection were the primary level of education (OR = 7.97; 95% CI = 2.23 to 28.49, P = 0.001) and multiple sexual partners (OR = 4.82; CI 95% = 2.24 to 10.38, P = 0.002). Conclusion. The low level of education and multiple sexual partners are significantly associated with HIV infection. We recommend the education of the girls which is a key factor for the empowerment of women. RÉSUMÉ Introduction. L’infection par le VIH affecte des millions de personnes en Afrique subsaharienne. Les modes de transmission sont multiples parmi lesquels la transmission de la mère à l’enfant. L’objectif principal de cette étude était de déterminer les facteurs de risque d’infection par le VIH chez les femmes enceintes de l’unité de maternité de l’Hôpital Central de Yaoundé. Méthodologie. Nous avons mené une étude analytique transversale à l’Unité de gynécologique et obstétrique de l’hôpital central de Yaoundé du 6 octobre 2015 au 30 juin 2016. L’échantillonnage était consécutif. Les tests du VIH ont été effectués par un test sensible et un test spécifique si le premier était positif. L’analyse des données a été réalisée à l’aide du logiciel EpiData Analysis Version 3.2 et STATA version 12.0 (Texas USA 2001). La signification statistique a été acceptée pour une valeur de P <0,05. Résultats. Nous avons inclus 360 femmes enceintes. Leur âge moyen était de 27,99 +/- 5,63 ans, avec des extrêmes allant de 15 à 47 ans. La prévalence du VIH dans cette population était de 13,1% (47/360). Les principaux facteurs de risque d’infection par le VIH ont été le niveau d’éducation primaire (OR = 7,97; IC à 95% = 2,23 à 28,49 ; P = 0,001) et plusieurs partenaires sexuels (OR = 4,82; IC 95% = 2,24 à 10,38 ; P = 0,002). Conclusion. Le faible niveau d’éducation et les multiples partenaires sexuels sont les principaux facteurs de risque de l’infection à VIH chez les femmes enceintes. Nous recommandons de promouvoir l’éducation de la jeune fille qui est un facteur clé pour l’autonomisation des femmes.